PROFIL PENILAIAN KEPALA SEKOLAH TERHADAP MAHASISWA ALUMNI PROGRAM STUDI PGSD FKIP UPY - Dhiniaty Gularso (Universitas PGRI Yogyakarta, 2014)
This study aimed to obtain information about the Principal Assessment Profile Against Student Program Guidance and Counseling PGSD UPY which includes integrity ( moral and ethical ), science based skills ( professionalism ), English skills , use of information technology, communication skills, teamwork abilities, and self-development. This research is descriptive quantitative. The subjects of this study were primary school head who supervises the course graduates PGSD FKIP UPY . The target for this study were at least 50 elementary schools will be used as the study sample of 266 scattered throughout Indonesia, meaning that the selection of the sample using purposive sampling method . This is done with consideration of the alumni who are spread throughout Indonesia. The results showed that 56 or 21 % of alumni successfully tracked. Assessment of the overall competence of the principal of includes integrity (moral and ethical) , science based expertise ( professionalism ) , English proficiency , the ability to use ICT, communication skills, ability to work in teams and develop self kemempuan 34.86 % is very good , 53.00 % , 10.86 % and 1:28 % enough school principals less.